Pragmatic utopias : ideals and communities, 1200-1630 - Horrox, Rosemary; Rees Jones, Sarah (Cambridge University Press, 2001)
Spanning the artificial divide between medieval and early modern, these essays show how men and women tried to put their ideals into practice, sometimes alone, but more commonly in the shared environment of cloister, college or city. The volume will be welcomed by all scholars of pre-modern religion and society.